Relapse-like behavior in a mouse model of the OPRM1 (mu-opioid receptor) A118G polymorphism: Examination with intravenous oxycodone self-administration. (15th December 2020) - Zhang, Yong; Collins, Devon; Butelman, Eduardo R.; Blendy, Julie A.; Kreek, Mary Jeanne
Abstract: The widely abused prescription opioid oxycodone is a mu-opioid receptor (MOP-r) agonist and addiction to such opioids is a relapsing disorder. The human MOP-r gene ( OPRM1 ) has an important functional single nucleotide polymorphism (SNP), A118G, which affects risk of severe opioid use disorders. A112G (G/G) knock-in mice are models of human A118G carriers. We examined oxycodone self-administration (SA) in male and female G/G versus wild type (A/A) mice in SA sessions and in relapse-like behavior. Adult male and female G/G and A/A mice self-administered oxycodone (0.25 mg/kg/infusion, FR1) for 10 consecutive days. Following 10-day home cage drug free withdrawal, the mice were re-exposed to oxycodone SA for a further 10 days. MOP-r receptor mRNA in various brain regions were examined immediately after the last re-exposure session. We found that G/G mice had greater oxycodone SA than A/A mice in the initial and in re-exposure sessions. Mice of both genotypes had greater oxycodone intake during the re-exposure period than during the initial exposure. We also detected differences in MOP-r gene expression due to genotype, sex and oxycodone SA history in the dorsal striatum, hippocampus, and prefrontal cortex. These studies may improve our understanding of MOP-r-agonist self-exposure and relapse in human carriers of the A118G SNP. Highlights: A112G mice self-administered more oxycodone during initial acquisition. A112 G mice self-administered more oxycodone during re-exposure. Mice took more oxycodone during re-exposure than during initial SA.